2019
DOI: 10.3389/fchem.2019.00369
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor-Directed Molecular Conjugates for Targeting Prostate Cancer

Abstract: Due to its central role in the cellular biology of prostate cancer (PC), androgen receptor (AR) still remains an important therapeutic target for fighting this tumor. Several drugs targeting AR have been reported so far, and many new molecules are expected for the future. In spite of their antitumor efficacy, these drugs are not selective for malignant cells and are subjected to AR-mediated activation of drug resistance mechanisms that are responsible for several drawbacks, including systemic toxicity and dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The androgen receptor gene is located on the X chromosome at location Xq11-12. It is well known that AR represents a vital driving force in the development and progression of prostate (Beretta & Zaffaroni, 2019) and the signaling pathway of AR plays important roles in prostate carcinogenesis and metastatic or androgen-independent progression of the disease (Tien & Sadar, 2019). In addition, Mills (2014) reported that AR involves in PCa development by affecting genomic stability and DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…The androgen receptor gene is located on the X chromosome at location Xq11-12. It is well known that AR represents a vital driving force in the development and progression of prostate (Beretta & Zaffaroni, 2019) and the signaling pathway of AR plays important roles in prostate carcinogenesis and metastatic or androgen-independent progression of the disease (Tien & Sadar, 2019). In addition, Mills (2014) reported that AR involves in PCa development by affecting genomic stability and DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic drugs target a differential feature of cancer cells that help them to actively proliferate. The main types of chemotherapy agents used in the clinics are: alkylating agents and platinants (damage DNA), such as cisplatin (101); cytotoxic antibiotics (bind DNA to prevent DNA and/or RNA synthesis); inhibitors of topoisomerase (damage DNA), such as daunorubicin, doxorubicin, irinotecan and etoposide; antimetabolites (interfere with intermediary metabolism of proliferating cells), such as gemcitabine; anti-microtubule agents (target microtubules and associated proteins required in cell division), such as paclitaxel and docetaxel (102); hormonal agents (inhibit hormone synthesis or function as hormone receptor agonist/antagonist) (103), such as tamoxifen or enzalutamide; and immunotherapy (target cancer cells that express a specific antigen or boost the natural ability of T cells to fight cancer), such as trastuzumab.…”
Section: Targeting Cancer Metabolism To Overcome Drug Resistancementioning
confidence: 99%
“…Many AR-degrading PROTACs exist, however, ARCC-4 ( 26 ) is shown here as an exemplary SARD [ 40 , 45 , 46 ]. ARCC-4 ( 26 ) in Figure 4 utilizes 3 as the AR ligand and VHL as the ubiquitin ligase, thereby targeting AR to the protease for degradation.…”
Section: Need For Ar-directed Therapy Beyond Canonical Antiandrogementioning
confidence: 99%